2011
DOI: 10.4297/najms.2011.3201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating trial of scar in patients with a history of caesarean section

Abstract: Aims:To analyze the outcome of trial of scar in patients with previous caesarean section and to assess the fetal and maternal complications after trial of scar.Patients and Methods:The study was conducted at Military Hospital, Rawalpindi, Pakistan, with 375 pregnant patients who had a previous delivery by caesarean and who had regular antenatal checkup. Data were recorded on special pro-forms designed for the purpose.Results:The results from the 375 patients who had one previous lower segment caesarean section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…These findings are in agreement with some studies [19,24] and in conflict with others [25] that demonstrated a higher rate of adverse neonatal outcome in association with failed trial of scar, nonavailability of modern neonatology equipment, or increased uterine rupture rate.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with some studies [19,24] and in conflict with others [25] that demonstrated a higher rate of adverse neonatal outcome in association with failed trial of scar, nonavailability of modern neonatology equipment, or increased uterine rupture rate.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with some studies [28,29,33,37], but disagree with others [6,32] that demonstrated a higher rate of adverse neonatal outcome in association with a failed trial of scar, non-availability of modern neonatology equipment, or increased uterine rupture rate.…”
Section: Commentssupporting
confidence: 84%
“…Vaginal birth after cesarean section (VBAC) is settled from the 1980 National Institutes of Health (NIH) Consensus Conference on Cesarean as a tool to minimize the cesarean delivery rate [5]. The present medical studies show that 60% -80% of women can attain successful trial of labor after a previous cesarean section [6].…”
Section: Introductionmentioning
confidence: 99%
“…The low transverse incision has approximately 0.2%-0.5% incidence of uterine rupture with VBAC. 6 For success of VBAC, scar rupture should be anticipated. Use of obstetric risk assessment before trial of scar, continuous electronic fetal heart rate monitoring and intrauterine pressure monitoring during labor will help in anticipation.…”
Section: Introductionmentioning
confidence: 99%
“…Late signs include cessation of uterine activity, hematuria, loss of station of the presenting part and maternal shock. 6 The subject of the delivery of a woman after a previous one cesarean section remains controversial. However, we should keep in mind that patients with successful trial of labor experience fewer complications like blood transfusions, postpartum infections and no increase in perinatal mortality as compared to those with planned repeat caesarean delivery.…”
Section: Introductionmentioning
confidence: 99%